SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF FEW CHALCONES - K. PRASADARAO; A. J. LUSIRANI SUSUMA; S. MOHAN (International Journal of Pharma and Bio Sciences, 2012)
In an effort to develop anti-bacterial agents, a series of Chalcones were synthesized by condensing 4-chloro, 2-hydroxyacetophenone with aldehyde derivatives in dilute ethanolic sodium hydroxide solution at room temperature according to claisen-schmidt condensation. The synthesized compounds were characterized by means of their IR, 1H-NMR spectral data and elemental analysis. All these compounds were tested for their anti-bacterial activity by agar well diffusion method.